Retrospective data analysis of animal poisoning events in Liguria. (September 2021) - Avolio, R.; Andreoli, T.; Ercolini, C.; Mignone, W.; Beltrame, R.; Razzuoli, E.; Modesto, P.; Zoppi, S.; Crescio, M.I.; Ostorero, F.; Gili, M.; Abete, M.C.; et al.
Highlights: Confirmed animal poisoning cases were 215/497 (43.2%) from 2009 to 2018. Anticoagulant rodenticides (79.2%) were the main cause of animal poisoning. The most affected areas are located along the coast. Dogs and cats were 40.0% of confirmed animal poisoning. Abstract: Intentional poisoning represents a serious risk to domestic and wild animals, and it can be an environmental and human health issue as well . This paper is a retrospective study, which covers a decade, based on animal poisoning cases and poisoned baits that were submitted for diagnostic examinations to the Veterinary Medical Research Institute for Piedmont, Liguria and the Aosta Valley (IZS-PLVA) in Liguria region. All data were collected through a passive surveillance system introduced in Italy by a decree of the Ministry of Health in January 2009. 43.2% of the animal poisoning cases were confirmed by toxicological analysis, whereas toxic agents were detected in 31.1% of the baits. The most affected animal species were dogs and cats, followed by synanthropic birds, . Only 4% of the total poisoning events analysed involved wild animals and cases of livestock poisoning were minimal. An increased number of cases in January, March, April and August was noticed, but no seasonal trend was detected. The most affected areas were the ones with the highest level of urbanization and population density. The major cause of the poisonings and the most common substances detected in the examined baits were anticoagulants whereas cholinesterase inhibitors, organochlorine pesticides and carbamates were detected in a minor number of cases. This study raises concerns about deliberate animal poisoning in ligurian region and highlights the necessity to fight this phenomenon as it endangers animals, humans and environment.